Introduction to the Special Series “Environmental Monitoring on Global and Local Scales” - Zotina, Tatiana A.; Kudryasheva, Nadezhda S.; Soukhovolsky, Vladislav G. (Integrated environmental assessment and management, 2023)
The ecosystems of Siberia provide valuable services to the human population and afford important climate feedback. However, they are subject to anthropogenic pressures leading to the transformation of ecosystem structure and functions such as deforestation; extraction and transportation of fossil hydrocarbons; mining, refining, and smelting industrial activities; damming of rivers by high‐pressure hydroelectric plants, and other activities. The articles in this special series deal with the monitoring of natural ecosystems of Siberia that are located on vast areas of Eurasia, many of which are hard to reach and sparsely populated. The results and approaches of environmental monitoring presented in this special series offer new opportunities for developing the strategy of intelligent management and conservation of vulnerable Siberian ecosystems to meet the challenges of global climate change and unsustainable use of natural resources. Integr Environ Assess Manag 2023;19:970–971. © 2023 SETAC Key Point The approaches of environmental monitoring presented in this special series offer new opportunities for developing the strategy of intelligent management and conservation of Siberian ecosystems to meet the challenges of global climate change and unsustainable use of natural resources.